The Use of Grammar Learning Strategies by Libyan EFL Learners at Sebha University - Safia Mujtaba Alsied; Noura Winis Ibrahim; Mustafa Mubarak Pathan (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2018)
For most English  language  learners, grammar can be  a very hard subject and some students tend to use different types of  strategies to learn grammar. Using learning strategies is very beneficial as they facilitate the learning process and make it more controlled, enjoyable  and effective for learners. This study explores the grammar learning strategies used by Libyan EFL undergraduate  students  at the English Department of Sebha University and the most  frequents used strategies. The  study also aims to find out if there is a significant difference between the students' use of learning strategies and gender. The population of the study  were  121 Libyan EFL undergraduate students who are currently in  their first and second years.  Data was collected through questionnaire distributed to the participants in the class. The result  of the study revealed that Libyan EFL learners used different types of grammar learning strategies which included memory strategies, metacognitive strategies, socio-affective strategies and cognitive strategies which were the least frequent used ones. It was found that  the most frequent used strategies were memory strategies. The findings also  showed that there is no significant difference between the use of grammar learning strategies and the participants' genders.